PENGARUH PERUBAHAN IKLIM DAN TINGKAT PERSAINGAN TERHADAP KINERJA GRABBIKE DI BEKASI - Widuri, Gladis Sukma Ayu; Sari, Rycha Kuwara; Puspitorini, Ferawaty (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to examine the effect of climate change and competition level on the performance of GrabBike drivers in Bekasi. The background of this research is based on the fact that GrabBike drivers, as field workers, are highly vulnerable to external factors such as weather conditions and increasing competition among fellow partners. The research method used is quantitative with an associative approach. Data were collected through questionnaires distributed to 97 respondents selected using non-probability sampling with a quota sampling technique. Data analysis was performed using SPSS version 24, including validity tests, reliability tests, classical assumption tests, and hypothesis testing. The results of the study are: 1) Climate change (X1) has no positive and no significant effect on GrabBike driver performance (Y); 2) Competition (X2) has a positive and significant effect on GrabBike driver performance (Y); 3) Climate change (X1) and competition (X2) simultaneously have a positive and significant effect on GrabBike driver performance (Y).